Strategi Pemasaran Produk Hortikultura untuk Petani Kecil - Rivina Rahmatika; Silvia Ningsih; Wirdatul Husna; M. Rizki Ramadhani; Novia Yunanda; Erlita E (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Small scale horticultural farmers encounter significant challenges in marketing their products, including limited market access, price volatility, and financial constraints. This study examines effective marketing strategies to improve farmers’ income and product competitiveness. A qualitative descriptive approach was employed, using in-depth interviews with 30 horticultural farmers in District Bireuen. The results reveal that effective strategies include strengthening partnerships with local traders, adopting digital marketing platforms, diversifying products, and implementing direct marketing systems through farm-gate sales and modern markets. Overall, the integration of traditional and modern marketing strategies enhances market access and contributes to improved welfare among small-scale farmers.